2020
DOI: 10.1007/s11082-020-2212-2
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural-chemistry of SnS nanocrystals prepared by thermal decomposition of bis(N-di-isopropyl-N-octyl dithiocarbamato)tin(II) complex for promising materials in solar cell applications

Abstract: Mixed ligand precursor complex bis(N-di-isopropyl-N-octyl dithiocarbamato)tin(II) complex was synthesized from its respective dithiocarbamate ligands, characterized and thermalized through thermogravimetric analysis to yield tin sulfide (SnS) nanocrystals. The thermal decomposition pattern was recorded as a function of the required temperature for the formation of the SnS nanocrystals at 360 °C. The SnS nanocrystals were characterized using optical, vibrational, structural and morphological analyses instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Synthesis of CuS nanocrystals was obtained through the high-temperature thermal decomposition of (bis(N-1,4-phenyl-N-(4-morpholinedithiocarbamato)copper(II)) complexes according to [66] using a Perkin Elmer 4000 ThermoGravimetric Analyser. Approximately 25 mg of the complex was loaded into an alumina pan, and weight changes were recorded as a function of temperature for a 10 • C min −1 temperature gradient between 30 and 900 • C. A purge gas of flowing nitrogen at a rate of 20 mL min −1 was used.…”
Section: Synthesis Of Cus Nanoparticles Without Hda Capping Agentmentioning
confidence: 99%
“…Synthesis of CuS nanocrystals was obtained through the high-temperature thermal decomposition of (bis(N-1,4-phenyl-N-(4-morpholinedithiocarbamato)copper(II)) complexes according to [66] using a Perkin Elmer 4000 ThermoGravimetric Analyser. Approximately 25 mg of the complex was loaded into an alumina pan, and weight changes were recorded as a function of temperature for a 10 • C min −1 temperature gradient between 30 and 900 • C. A purge gas of flowing nitrogen at a rate of 20 mL min −1 was used.…”
Section: Synthesis Of Cus Nanoparticles Without Hda Capping Agentmentioning
confidence: 99%
“…In addition, there is no change in the preferential orientation along (201), (210), (111), (301), (311), (511), (610), and (512) for both samples, which confirms successful fabrication of SnS and SnS/HDA into the lattice of TiO2 [29]. The preferential orientation of SnS/HDA is linked to the nucleation control of the growth process due to excess HDA used during the synthesis [30]. The presence of lower intensities and minor phases are usually linked to defect chemistry, thermodynamics of solid, and thermal gradient.…”
Section: Resultsmentioning
confidence: 62%
“…In ATR-FTIR spectra of as-synthesized PDTC (Figure a), the peaks appearing at 2932 and 2867 cm –1 are due to pyrrolidine–CH 2 stretching vibrations in an asymmetric and symmetric manner . The C–N stretching vibration bands of the NCS were observed at 1465 and 1328 cm –1 . Peaks at 978 cm –1 can be correlated with CS of the −CSS – group, , whereas the C–S vibration band was found to be centered at 887 cm –1 . Further, the characteristic peaks at 549 and 483 cm –1 due to the stretching vibration of the Cu–S bond strongly support the formation of the Cu­[PDTC] 2 complex (Figure c).…”
Section: Resultsmentioning
confidence: 97%
“…Further, the characteristic peaks at 549 and 483 cm −1 due to the stretching vibration of the Cu−S bond strongly support the formation of the Cu[PDTC] 2 complex (Figure 1c). From the literature survey, it has been found that the stretching vibration frequency of the metal sulfur (M−S) bond (such as Zn−S, 73 Co−S, 78 Sn−S, 77 etc.) appears between 475 and 580 cm −1 .…”
Section: ■ Introductionmentioning
confidence: 99%